GENRE ANALYSIS THE FILM GUNDALA - Sinulingga, Kinanthi N.V.M.; Wibawa, Satrya (Capture : Jurnal Seni Media Rekam, 2022)
Gundala (2019) is the latest Indonesian action film that was commercially successful, won national and international awards, and even ranked second in viewership in 2019. This study aims to identify the genre characteristics of Gundala. This paper utilized Nick Lacey's genre analysis, which analyzes films based on the repertoire of elements (narratives, characters, settings, iconography, and styles). The research shows that Gundala adopted the action genre characteristics, especially in the narrative, character, and style. However, the setting and iconography of the film have been modified to fit the local cultural context. Hence, the distinctiveness of Indonesian films can expand similar studies in film genres.